Genetic and Environmental Influences on the Development and Stability of Executive Functions in Children of Preschool Age: A Longitudinal Study of Japanese Twins. Issue 3 (5th July 2016) - Fujisawa, Keiko K.; Todo, Naoya; Ando, Juko
Abstract : Executive functions (EF) are an important predictor of later adaptive development. A number of environmental influences, such as parenting, have been suggested as important promoters of EF development. However, behavioural genetic research has demonstrated that many environmental influences could be affected by genetic influences. Therefore, it is important to consider genetic variations when investigating environmental influences on EF development in children. To date, few studies have used genetically informative designs to assess the etiology of EF development during the preschool years, a period of rapid development. As a result, it remains unclear how and to what extent the environmental influences that are not confounded by genetic influences affect EF development during this developmental period. The present study explored EF development during the preschool years using a longitudinal and genetically informative design and a non‐Western population. Japanese twins were visited at their homes and individually tested on EF measures at 24, 36, and 48 months of age. Phenotypic correlations and confirmatory factor analyses suggested that EF are less cohesive at 24 months of age and emerge as a common single factor at 36 and 48 months. Additionally, longitudinal and multivariate behavioural genetic analyses indicated that the EF developmental change during this period is promoted by both shared and nonshared environmental influences as well as genetic influences, while EF stability is brought about by shared environments. The present findings elucidated the etiology of EF development during the preschool years and confirmed that this period is an important transitional stage for EF development. Copyright © 2016 John Wiley & Sons, Ltd.